Special Education and teacher training: disciplinary programs analysis that discuss the thematics in UFRN in the last years (1999-2016) (Research, Society and Development, 2017)
The present study is one of the ramifications of the research project entitled: People with Disabilities Inclusion at UFRN: Education, Work and Knowledge Production. The aim of this research is to analyze the disciplines programs of graduation of UFRN that discuss Special Education from 1999 to 2016 in order to verify the evolutions and the stagnations in the course of time within these curricular components and the main topics discussed in the last years in the disciplines. The research is documental with a qualitative approach, in which the content analysis is based on Bardin (2011). We understand the necessity of thinking about teacher training considering the current social demands and the challenges that they impose on the education professionals, among those the necessity of thinking about the inclusion professor of the disabled person mediated by Special Education. The disciplines vary during the years between 60h and 90h, some themes have been appearing during the investigated time repeatedly, such as "Family" and "Society". Weobserved advances in the programs following the social inclusion legal references and the academic discussions about the thematic, as the change in terms used in the discussions related to Special education. Therefore, we understand that some aspects are permanents in the inclusion teacher training, and others suffers changes in the course of time in order to follow the flow of society.